Regional Asset Management Analysis In Kupang District - Aldarine Molidya; Cicilia A. Tungga; Rikhard T. Ch. Bolang (Eduvest - Journal of Universal Studies, 2022)
This research aims to analyze the level of the importance and the performance of the implementation of factorsn or attribute that determine the successful asset management in Kupang District Government. Importance Performance Analysis (IPA) is used as an analysis tool to process research data. The results showed that asset management has not been fully optimal. This can be seen from the results of data analysis that is unbalancing between importance and performance levels. There are two attributes of questions that are classified in the quadrant III category, namely attributes or factors P1 and attributes or factors P9. This attribute reflects the activities of collecting regional asset data within the Kupang district government and the use of an asset inventory book that is still necessary to maintain its performance and activities. This is related to the procedure for managing regional property as mandated in the Regulation of the Minister of Home Affairs (Permendagri) Number 19 of 2016 concerning Guidelines for the Management of Regional Assets.